Safety of Combination Biologic and Antirejection Therapy Post–Liver Transplantation in Patients With Inflammatory Bowel Disease. Issue 6 (28th October 2019) - Al Draiweesh, Saleh; Ma, Christopher; Alkhattabi, Maan; McDonald, Cassandra; Nguyen, Tran M; Beaton, Melanie; Chande, Nilesh; Colquhoun, Patrick; Feagan, Brian G; Gregor, James C; Khanna, Reena; Marotta, Paul; et al.
Abstract : Patients with inflammatory bowel disease post–liver transplant may have inflammation requiring biologic therapy. We aimed to evaluate the safety of combination biologic and antirejection therapy in inflammatory bowel disease patients after liver transpant from a tertiary center case series and an updated literature review. Abstract: Background: Patients with inflammatory bowel disease (IBD) post–liver transplant (LT) may have bowel inflammation requiring biologic therapy. We aimed to evaluate the safety of combination biologic and antirejection therapy in IBD patients after LT from a tertiary center case series and an updated literature review. Methods: Inflammatory bowel disease patients undergoing LT between 1985 and 2018 and requiring combination biologic and antirejection therapy post-LT were identified from the London Health Sciences Transplant Registry (Ontario, Canada). Safety outcomes were extracted by medical chart review. For an updated literature review, EMBASE, Medline, and CENTRAL were searched to identify studies evaluating the safety of combination biologic and antirejection therapy in IBD patients. Results: In the case series, 19 patients were identified. Most underwent LT for primary sclerosing cholangitis (PSC; 14/19, 74%) treated with anti-integrins (8/19, 42%) or tumor necrosis factor α (TNF) antagonists (6/19, 32%). Infections occurred in 11/19 (58%) patients, most commonly Clostridium difficile (4/19, 21%). Two patients required colectomy, and 1 patient required re-transplantation. In the literature review, 13 case series and 8 case reports reporting outcomes for 122 IBD patients treated with biologic and antirejection therapy post-LT were included. PSC was the indication for LT in 97/122 (80%) patients, and 91/122 (75%) patients were treated with TNF antagonists. Infections occurred in 32/122 (26%) patients, primarily Clostridium difficile (7/122, 6%). Conclusions: Inflammatory bowel disease patients receiving combination biologic and antirejection therapy post-LT appeared to be at increased risk of Clostridium difficile . Compared with the general liver transplant population in the published literature, there was no increased risk of serious infection.